Technology, Competitiveness And Radical Policy Change : the Case Of Brazil. - Meyer-stamer, Jorg (Taylor & Francis Ltd., 1997)
This volume investigates the limited effectiveness of technology policy in the inward-oriented industrialization model of the past.